Preparation and properties of hydrous bismuth oxides for nitrate removal from aqueous solutions - Singh P.K.; Srivastav A.L.; Ghosh D.K.; Sharma Y.C. (My University, 2025)
With an ultimate objective of developing an inorganic sorptive media for nitrate removal from water for drinking purpose, preparation and properties of hydrous bismuth oxides (HBOs) were studied. Three HBOs, designated as HBO1, HBO2 and HBO3 were prepared using 0.1 M Bi2O3 solution in 2 N HCl and 2 N NaOH in 1:1, 1:2 and 1:3 volumetric proportions respectively. In column tests, with 1 meq l−1 (=14 mg N l−1) nitrate in distilled water as influent solution, HBO1, HBO2 and HBO3 were found to remove 0.6, 1.2 and 1.4 mg N g−1 (dry mass basis) at controlled flow rates of 1.20–1.45, 1.45–2.10 and 1.30–2.10 ml min−1 from the respective columns. Regeneration attempt of the used media by passing 0.1 N NaOH solution gave a nitrate recovery ratio (RR) of 0.9 for HBO1 and HBO2 and 0.5 for HBO3. In the second cycle of nitrate laden water application, whereas HBO2 and HBO3 showed decreased nitrate removals, HBO1 exhibited increased uptake. On dry mass basis HBO1, HBO2 and HBO3 precipitates showed a nitrate removal of 1.1, 0.7, and 1.0 mg N g−1 respectively in the second cycle. Thus, in two cycles HBO1, HBO2 and HBO3 precipitates were found to remove 1.7, 1.9 and 2.4 mg nitrate from solution per g (dry mass) respectively. The effluent pH remains fairly in the range of 7.0 to 8.9, indicating that OH− ions are not released from HBOs in significant quantity due to nitrate sorption. The precipitates apparently held appreciable amount of chloride which may play important role in nitrate removal process. © 2012 Elsevier Inc.